Organic Amendment on Soil Quality and Yield Performance of Dry Direct Seeded Boro Rice (Bangladesh Agronomy Journal, 2021)
An experiment was conducted at Khitrokashipur, Durgapur, Rajshahi during March to June 2018 to study the effect of organic amendment on soil quality and yield performance of dry direct seeded boro rice var. BRRI dhan28. The treatments were Trichocompost (TC), Vermicompost (VC), mustard oil cake (MOC), Trichocompost + mustard oil cake (TC+MOC), Vermicompost + mustard oil cake (VC + MOC), and no amendment control. The experiment was laid out in a randomized complete block design with three replications. Trichocompost and Vermicompost were applied @ 3 t ha-1, while mustard oil cake was used @ 0.5 t ha-1. The results revealed that Trichocompost and vermicompost fertilization exerted significant influence on yield performance of BRRI dhan28 in boro season. The treatment trichocompost (T1) @ 5 t ha-1 produced the highest grain yield (5.95 t ha-1), while the mustard oil cake (T3) @ 0.5 t ha-1 the highest effective tillers hill-1 (15.33), though  the highest straw yield (5.46 t ha-1) was produced in the treatment VC + MOC (T5). In case of soil properties, Trichocompost (T1) @ 3 t ha-1 and mustard oil cake (T3) @ 0.5 t ha-1 improved soil organic matter content, while Trichocompost (T1) @ 3 t ha-1 and Vermicompost (T2) @ 0.5 t ha-1 improved phosphorus and potassium content. Field capacity was greatly influenced by Trichocompost (T1) @ 3 t ha-1 and Vermicompost + mustard oil cake (T5). Soils with Trichocompost (T1) @ 3 tha-1 showed the highest bulk density. It was concluded that organic amendment greatly improved the yield performance of BRRI dhan28 and also soil physical and chemical properties under dry direct seeded boro rice cultivation system.Bangladesh Agron. J. 2020, 23(2): 103-109